Pengaruh Gaya Kepemimpinan dan Kinerja Karyawan terhadap Kepuasan Pelanggan PT Catur Putra Jaya Bekasi Utara - Georgius Mansuetus Leong; Zahra Zahra; Athiy Dina Rosihann (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of leadership style and employee performance on customer satisfaction at PT Catur Putra Jaya, North Bekasi. Employee performance is one of the crucial factors influencing the company’s stability, productivity, and long-term development. An effective leadership style is believed to create a conducive work environment, motivate employees to work more efficiently, and improve services that directly impact customer satisfaction. This research employs a quantitative approach using a survey method by distributing questionnaires to 50 respondents who are employees of PT Catur Putra Jaya. The data were analyzed using multiple linear regression to examine both the simultaneous and partial effects of leadership style and employee performance on customer satisfaction. The results show that leadership style and employee performance simultaneously have a significant effect on customer satisfaction. Partially, both variables also have a positive and significant influence. These findings emphasize that improving leadership quality and optimizing employee performance are key factors in enhancing customer satisfaction and strengthening the company’s positive image amid increasing business competition.